Peran Permainan Petak Umpet Dalam Membentuk Kemandirian Anak Usia Dini - Safitri, Nuralia; Yuliani; Ulfa, Maria; Herman; Rusmayadi (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to find out the role of umpet play in increasing the responsibility and independence of early childhood. The type of research used is a library study, with data collection from various journals and the recording of relevant information. Data analysis uses three interactive analysis models, namely data reduction, data display, and conclusion overview. Data validation is done by triangulation. The results of the study showed that puzzle games can form early childhood independence, but need to be developed continuously according to the social, emotional, and physical conditions of each child. Overall, the study concluded that Puzzle games have a positive role in increasing responsibility and independence of early children, as long as they are developed properly in accordance with each child's development.